In‐depth protein profiling of the postsynaptic density from mouse hippocampus using data‐independent acquisition proteomics. Issue 21 (18th October 2014) - Distler, Ute; Schmeisser, Michael J.; Pelosi, Assunta; Reim, Dominik; Kuharev, Jörg; Weiczner, Roland; Baumgart, Jan; Boeckers, Tobias M.; Nitsch, Robert; Vogt, Johannes; Tenzer, Stefan
<x xml:space="preserve">Abstract</x> Located at neuronal terminals, the postsynaptic density (PSD) is a highly complex network of cytoskeletal scaffolding and signaling proteins responsible for the transduction and modulation of glutamatergic signaling between neurons. Using ion‐mobility enhanced data‐independent label‐free LC‐MS/MS, we established a reference proteome of crude synaptosomes, synaptic junctions, and PSD derived from mouse hippocampus including TOP3‐based absolute quantification values for identified proteins. The final dataset across all fractions comprised 49 491 peptides corresponding to 4558 protein groups. Of these, 2102 protein groups were identified in highly purified PSD in at least two biological replicates. Identified proteins play pivotal roles in neurological and synaptic processes providing a rich resource for studies on hippocampal PSD function as well as on the pathogenesis of neuropsychiatric disorders. All MS data have been deposited in the ProteomeXchange with identifier PXD000590 (http://proteomecentral.proteomexchange.org/dataset/PXD000590).